2006
DOI: 10.1124/jpet.106.106781
|View full text |Cite
|
Sign up to set email alerts
|

Regional Hemodynamic Effects of Neutral Endopeptidase Inhibition and Angiotensin (AT1) Receptor Antagonism Alone or in Combination in Conscious Spontaneously Hypertensive Rats

Abstract: We tested the hypothesis that angiotensin (AT 1 ) receptor antagonism (with losartan) would enhance the cardiovascular actions of neutral endopeptidase (NEP) inhibition [with candoxatrilat or (2S)-2-{[1-({[(1S)-1-carboxy-2-(5-phenyl-1,3-oxazol-2-yl)ethyl]amino}carbonyl)cyclopentyl]methyl}-4-methoxybutanoic acid (UK-489,329)] in conscious spontaneously hypertensive rats (SHR). Four-day continuous intravenous infusion of candoxatrilat (1.9 g kg Ϫ1 min Ϫ1 ) or UK-489,329 (0.15 g kg Ϫ1 min Ϫ1 ) had no significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In the present study, the plasma concentration of candoxatrilat, the active metabolite of candoxatril, reached 7.82±0.64 μg ml −1 after a 10 mg kg −1 30‐min infusion. This concentration is above those previously demonstrated to produce a modest antihypertensive effect in conscious spontaneously hypertensive rats ( Gardiner et al , 2006 ), but it is a concentration at which selectivity for NEP would be expected, since even at vastly higher concentrations (up to 0.1 m M ) candoxatrilat was shown to exert no inhibitory activity at other well‐known peptidases, including ACE, carboxypeptidase A, leucine aminopeptidase, trypsin, chymotrypsin and renin ( Northridge et al , 1989 ; Barclay et al , 1991 ).…”
Section: Methodsmentioning
confidence: 73%
“…In the present study, the plasma concentration of candoxatrilat, the active metabolite of candoxatril, reached 7.82±0.64 μg ml −1 after a 10 mg kg −1 30‐min infusion. This concentration is above those previously demonstrated to produce a modest antihypertensive effect in conscious spontaneously hypertensive rats ( Gardiner et al , 2006 ), but it is a concentration at which selectivity for NEP would be expected, since even at vastly higher concentrations (up to 0.1 m M ) candoxatrilat was shown to exert no inhibitory activity at other well‐known peptidases, including ACE, carboxypeptidase A, leucine aminopeptidase, trypsin, chymotrypsin and renin ( Northridge et al , 1989 ; Barclay et al , 1991 ).…”
Section: Methodsmentioning
confidence: 73%
“…45 Thus, losartan may increase the CD through its vasodilator action or hypotensive effect. 46 In addition to the vasodilator or hypotensive effect, the proangiogenic effect of losartan may also be mediated by the following mechanism: ARB blocks AT1 receptors, whereas unbound angiotensin II stimulates AT2 receptors, which in turn increase angiogenic factors, such as vascular endothelial growth factor receptors, Tie-2 expression and the angiopoietin-1/angiopoietin-2 ratio. 47 In addition, You et al 48 reported that losartan administration resulted in an improvement in hindlimb ischemia-induced capillary rarefaction, and this improvement was associated with a restoration of progenitor cell-related function in spontaneously hypertensive rat.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, there have been a few attempts to characterize the hemodynamic effects of simultaneous inhibition of the AT 1 receptor and NEP. 31,32 Recently, the preclinical and clinical antihypertensive profile of LCZ696, a fixed dose combination of valsartan (an ARB) and AHU-377 (an NEP inhibitor prodrug) has been reported. 33,34 Despite these advances, a systematic comparison of relative efficacy and the risk for angioedema for such a combination and its comparison to omapatrilat have not been established.…”
Section: Introductionmentioning
confidence: 99%